If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6=-3x+36x=
We move all terms to the left:
6-(-3x+36x)=0
We add all the numbers together, and all the variables
-(+33x)+6=0
We get rid of parentheses
-33x+6=0
We move all terms containing x to the left, all other terms to the right
-33x=-6
x=-6/-33
x=2/11
| x^2+120x-4|500=0 | | 10p-50=5000 | | -3(5a+6)=2(3a+8) | | Z3=8i | | -(5x-3)=3x+2 | | s*6+40=184 | | 8p-16=56 | | 6(x+2)-7x=-14 | | 2.20g=53.90 | | 7^(x-3)+7^(x-2)+7^(x-1)=57 | | 5x+52+6x=25 | | -0=x+5 | | 2x=100x= | | x-20+2x=25 | | 125^3x+7=25^5x−11 | | (10)^2x+1=3 | | -7g−8=-8g | | s/4+4=15 | | 5(g=8)-7=103 | | 9t+20=7t-12 | | 24,000-4000/3x=4000 | | 4w-2+2w=28 | | +22x=53.90 | | 10^2x+1=3 | | 15s-20=375 | | 3x=2x+503x=2x+50 | | 12n-5=27 | | -4(2k+4)=-2(4-3k) | | 250+150x=26 | | 12y=13y-6 | | 3x2+19x=14 | | 7/2=w-3/2 |